Evolution of a clade of Acinetobacter baumannii global clone 1, lineage 1 via acquisition of carbapenem- and aminoglycoside-resistance genes and dispersion of ISAba1. Issue 1 (16th January 2019) - Hamidian, Mohammad; Hawkey, Jane; Wick, Ryan; Holt, Kathryn E.; Hall, Ruth M.
Abstract : Resistance to carbapenem and aminoglycoside antibiotics is a critical problem in Acinetobacter baumannii, particularly when genes conferring resistance are acquired by multiply or extensively resistant members of successful globally distributed clonal complexes, such as global clone 1 (GC1) . Here, we investigate the evolution of an expanding clade of lineage 1 of the GC1 complex via repeated acquisition of carbapenem- and aminoglycoside-resistance genes. Lineage 1 arose in the late 1970s and the Tn 6168 /OCL3 clade arose in the late 1990s from an ancestor that had already acquired resistance to third-generation cephalosporins and fluoroquinolones. Between 2000 and 2002, two distinct subclades have emerged, and they are distinguishable via the presence of an integrated phage genome in subclade 1 and AbaR4 (carrying the oxa23 carbapenem-resistance gene in Tn 2006 ) at a specific chromosomal location in subclade 2. Part or all of the original resistance gene cluster in the chromosomally located AbaR3 has been lost from some isolates, but plasmids carrying alternate resistance genes have been gained. In one group in subclade 2, the chromosomally located AbGRI3, carrying the armA aminoglycoside-resistance gene, has been acquired from a GC2 isolate and incorporated via homologous recombination. ISAba1 entered the common ancestor of this clade as part of the cephalosporin-resistance transposon Tn 6168 and has dispersed differently in each subclade. Members of subclade 1 share an ISAba1 in one specific position in the chromosome and in subclade 2 two different ISAba1 locations are shared. Further shared ISAba1 locations distinguish further divisions, potentially providing simple markers for epidemiological studies.